Analisis Bullwhip Effect Dalam Sistem Rantai Pasok Pada Produk PTA di PT. Mitsubishi Chemical Indonesia - Heru Winarno; Denny Kurnia; Muhammad Fahmi (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
Mitsubishi Chemical Indonesia is a producer of Purify Terepthalic Acid (PTA) in Indonesia with an important role in meeting the primary needs of the Indonesian population by managing raw materials to produce purified terepthalic acid. Purified terepthalic acid is the main raw material for polyester fiber. The problem that occurs is the phenomenon of the bullwhip effect, namely the occurrence of fluctuations between orders and demand which results in a shortage of raw materials or low inventory which can cause production to stop. So the purpose of this study is to calculate the value of the bullwhip effect, determine the causes of the bullwhip effect, and determine solutions to reduce the bullwhip effect. This study begins by calculating the value of the bullwhip effect at the two echelons. The method used in this research is FMEA. The results of this study are the value of the bullwhip effect at echelon 1 (suppliers and PPIC) = 1.27 and echelon 2 (PPIC and distributors) = 0.93. This value indicates the occurrence of a bullwhip effect in echelon 1 while echelon 2 does not indicate the occurrence of a bullwhip effect. The dominant causes of the bullwhip effect are market competition, rising material prices, demand forecasting that is not close to accurate and the number of orders for raw materials in large quantities. The proposed improvement is to collaborate with suppliers and customers to get guaranteed orders and demand that are fixed and sustainable. This value indicates the occurrence of a bullwhip effect in echelon 1 while echelon 2 does not indicate the occurrence of a bullwhip effect. The dominant causes of the bullwhip effect are market competition, rising material prices, demand forecasting that is not close to accurate and the number of orders for raw materials in large quantities. The proposed improvement is to collaborate with suppliers and customers to get guaranteed orders and demand that are fixed and sustainable. This value indicates the occurrence of a bullwhip effect in echelon 1 while echelon 2 does not indicate the occurrence of a bullwhip effect. The dominant causes of the bullwhip effect are market competition, rising material prices, demand forecasting that is not close to accurate and the number of orders for raw materials in large quantities. The proposed improvement is to collaborate with suppliers and customers to get guaranteed orders and demand that are fixed and sustainable.